Odpowiedź :
Odpowiedź:
p= pierwiastek
x= mnożenie
[tex]
\frac{2}{3+p2} = \frac{3}{3+p2} x \frac{3-p2}{3-p2} =\frac{6-2p2}{9-2} = \frac{6-2p2}{7} [/tex]
Odpowiedź:
[tex]\huge\boxed{\dfrac{2}{3+\sqrt2}=\dfrac{6-2\sqrt2}{7}}[/tex]
Szczegółowe wyjaśnienie:
[tex]\dfrac{2}{3+\sqrt2}[/tex]
skorzystamy ze wzoru skróconego mnożenia:
[tex]a^2-b^2=(a-b)(a+b)[/tex]
oraz z twierdzenia:
[tex](\sqrt{a})^2=a[/tex] dla [tex]a\geq0[/tex]
[tex]\dfrac{2}{3+\sqrt2}=\dfrac{2}{3+\sqrt2}\cdot\dfrac{3-\sqrt2}{3-\sqrt2}=\dfrac{2\cdot(3-\sqrt2)}{(3+\sqrt2)(3-\sqrt2)}=\dfrac{2\cdot(3-\sqrt2)}{3^2-(\sqrt2)^2}\\\\=\dfrac{2\cdot(3-\sqrt2)}{9-2}=\dfrac{2\cdot3-2\cdot\sqrt2}{7}=\dfrac{6-2\sqrt2}{7}[/tex]